Extraction of distinguished hyperbolic trajectories for 2D time‐dependent vector field topology - Hofmann, Lutz; Sadlo, Filip (Computer graphics forum, 2020)
This paper does two main contributions to 2D time‐dependent vector field topology. First, we present a technique for robust, accurate, and efficient extraction of distinguished hyperbolic trajectorie...